Experimental study of heat transfer in aerogel-coated insulated walls - Xiaolei Man; Chuanyao Peng; Zhiqiang Liao; Jincheng Zong; Hanyue Wang; Hui Liu (Journal of Engineering and Applied Science)
Abstract To investigate the heat transfer law of aerogel coating and clarify the optimal thickness of aerogel coating, the contact and noncontact heat transfer tests were carried out at different temperatures for the aerogel coating insulation wall composed of different thicknesses of aerogel coating and 6-cm cement board, and the thermal conductivity coefficients of the aerogel coating and the different parts of the coating were obtained by processing the test data at different thicknesses. The analysis shows that the contact method has little effect on the heat transfer law of the aerogel coating; 4 mm is recommended as the optimal thickness of the aerogel coating, and the thermal conductivity of the coating shows an increasing trend from the inside to the outside in the heat transfer process.